2009
DOI: 10.1002/cphc.200900130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Constrained Environment on the Interactions between the Surfactant and Different Polar Solvents Encapsulated within AOT Reverse Micelles

Abstract: Herein, we report a study of the interactions between different nonaqueous polar solvents, namely, ethylene glycol (EG), propylene glycol (PG), glycerol (GY), dimethylformamide (DMF), and dimethylacetamide (DMA), and the polar heads of sodium 1,4-bis-2-ethylhexylsulfosuccinate (AOT) in nonaqueous AOT/n-heptane reverse micelles. The goal of our study is to gain insights into the unique reverse-micelle microenvironment created upon encapsulation of these polar solvents. For the first time, the study is focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 55 publications
3
72
0
Order By: Relevance
“…[39][40][41][42] Durantini et al correlated changes in the AOT vibrational spectra with the reverse micelle size to find how a, the effective surfactant area, and P, the packing parameter, depend on the nonaqueous polar solvent properties. 43 In contrast with these nonaqueous microemulsions, the case of [ 4 ] and various molecules. Therefore, much still remains to be learned about these intriguing nanoheterogeneous systems both from the perspective of fundamental characterization and application of the reverse microemulsions for novel chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] Durantini et al correlated changes in the AOT vibrational spectra with the reverse micelle size to find how a, the effective surfactant area, and P, the packing parameter, depend on the nonaqueous polar solvent properties. 43 In contrast with these nonaqueous microemulsions, the case of [ 4 ] and various molecules. Therefore, much still remains to be learned about these intriguing nanoheterogeneous systems both from the perspective of fundamental characterization and application of the reverse microemulsions for novel chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…17 In n-hexane/AOT/water reverse micelles it was found that o-NA binds to the polar heads of AOT through the NH groups in a hydrogen bond interaction and, the water addition decreases the binding constant K b up to W 0 = 10 showing the competition of water for the polar heads of the surfactant. 17 Nevertheless, it is interesting to discover with which part of the AOT polar head, namely the sulfonate or the ester moiety 48 o-NA interacts through hydrogen bond. Thus, we have chosen a set of polar solvents that interact with different parts of the AOT moiety including the Na + counterions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, EG interacts weakly with the Na + counterion which seems to be close to the AOT sulfonate group as in the case of W S = 0. 48 In light of the above, we believe that o-NA has to interact by hydrogen bonding with the AOT sulfonate group rather than with the AOT's C=O group because the K b values obtained are lower for GY and water than EG. It seems that the competition for the AOT sulfonate solvation between -NH and water or GY dominates the binding process.…”
mentioning
confidence: 90%
See 2 more Smart Citations